Socio-Demographic and Risk factors associated with Knee osteoarthritis - Vinotha, S.; Ira, T.; Sri Ranjani, S. (Elixir International Journal, Elixir Orthopedics, 2017)
Knee Osteoarthritis (KOA) is a degenerative joint disease and a major public health problem all over the world. The present study is focused to evaluate the Socio-demographic and Risk factors associated with radiographic evidence of KOA subjects who were attended to Government Ayurveda Hospitals in Jaffna District from January 2013 to August 2014. There were 177 (70.8%) female and 73 (29.2%) male with a mean age of 57.02 (SD±8.78) years and highly significant association between age and gender (P<0.05) and BMI and gender (P<0.05) of KOA subjects. The findings of this study had indicated that risk factors as age, gender, family history, menopause and BMI were similar to the findings of KOA studies of other research studies.
Keywords: Association; Demography; Knee osteoarthritis; Risk factors